(untitled) (Research, Society and Development, 2021)
Selective Mutism is an anxiety disorder that is characterized by the child’s refusal to speak in certain places, especially at school. The aim of this study is to identify the factors associated with Selective Mutism, its behavioral changes, and difficulties in school development. To this end, an integrative, qualitative, exploratory literature review was carried out in electronic databases such as PUBMED, SCIELO, LILACS and ISI WEB OF SCIENCE. Data collection took place from September to October 2020, followed by a thorough evaluation of the studies found, which included an exploratory, selective, analytical, and interpretive reading. The final sample of this review was composed of 15 scientific studies, chosen by the inclusion criteria determined in advance. Through this study, it was possible to observe how the disturbances related to selective mutism interfere in educational or professional achievement or in social communication, presenting failure to speak in the presence of strangers. It was found that among the losses that this disorder causes in the child, it interferes mainly in the educational achievement (or in the future professional) or in the social communication. From the work developed, the idea arose that the end of silence in children with MS desired by parents, family, education, and health professionals, will not end overnight, it will be a long, slow and winding journey with progress and setbacks however, with the participation, effort, collaboration and dialogue of all stakeholders there will be a greater and faster chance of success in confronting the Ministry of Health.